Notes of statement by Sir William Beveridge to General Council at their meeting on 16 December, 1942 - Beveridge, William Henry Beveridge, Baron, 1879-1963
1942-12-17 1942 1940s 9 pages 4. say that the retail distributers should pay for dangers in mining, but there was no special reason why the shopkeeper rather than the shop assistant should pay. He wanted to take the administration out of the hands of the employers. He thought the employers could put up a strong argument that if they were to bear the whole cost, then the administration ought to remain with them. He pointed out that he was keeping a good part of the cost on the employers through the special levy in the dangerous industries. The third reason was that he didn't believe it desirable, if they had a whole lot of different services, to have one of them wholly at the cost of the employers with the insured person feeling no responsibility about it at all. They had got to look at the question as a whole. A person who was utterly incapacitated had the same needs as say other incapacitated person whatever had been the cause. For that reason he proposed the insurance stamp which was 7/6d. for an adult man - 4/3d. to be paid by the man and 3/3d. by the employer. Just over 3d. was the cost of the workmen's compensation cover. Paragraph 96 meant that out of the employee's 4/3d. there would be just over 1 1/3d. contribution to industrial accident and disease. He pointed out that it could be said that there was no reason why an employer should pay for widows and orphans benefit. The employer was to pay roughly 1.7 of a penny for this and the worker was paying 1 1/4d. for his accident. Sir William thought it was right not only to put part of the cost on the Insurance stamp, but to divide it like everything else, keeping the very substantial sum in the hazardous industries. AT THIS STAGE QUESTIONS WERE PUT TO SIR WILLIAM BEVERIDGE 292/150.5/5/2